Life and death of Picea abies after bark‐beetle outbreak: ecological processes driving seedling recruitment. Issue 1 (4th January 2017) - Macek, Martin; Wild, Jan; Kopecký, Martin; Červenka, Jaroslav; Svoboda, Miroslav; Zenáhlíková, Jitka; Brůna, Josef; Mosandl, Reinhard; Fischer, Anton
Abstract: The severity and spatial extent of bark‐beetle outbreaks substantially increased in recent decades worldwide. The ongoing controversy about natural forest recovery after these outbreaks highlights the need for individual‐based long‐term studies, which disentangle processes driving forest regeneration. However, such studies have been lacking. To fill this gap, we followed the fates of 2, 552 individual seedlings for 12 years after a large‐scale bark‐beetle outbreak that caused complete canopy dieback in mountain Norway spruce ( Picea abies ) forests in southeast Germany. We explore the contribution of advance, disturbance‐related, and post‐disturbance regeneration to forest recovery. Most seedlings originated directly within the three‐year dieback of canopy trees induced by bark‐beetle outbreak. After complete canopy dieback, the establishment of new seedlings was minimal. Surprisingly, advance regeneration formed only a minor part of all regeneration. However, because it had the highest survival rate, its importance increased over time. The most important factor influencing the survival of seedlings after disturbance was their height. Survival was further modified by microsite: seedlings established on dead wood survived best, whereas almost all seedlings surrounded by graminoids died. For 5 cm tall seedlings, annual mortality ranged from 20 to 50% according to the rooting microsite. However, for seedlings taller than 50 cm, annual mortality was below 5% at all microsites. While microsite modified seedling mortality, it did not affect seedling height growth. A model of regeneration dynamics based on short‐term observations accurately predicts regeneration height growth, but substantially underestimates mortality rate, thus predicting more surviving seedlings than were observed. We found that P. abies forests were able to regenerate naturally even after severe bark‐beetle outbreaks owing to advance and particularly disturbance‐related regeneration. This, together with microsite‐specific mortality, yields structurally and spatially diverse forests. Our study thus highlights the so far unrecognized importance of disturbance‐related regeneration for stand recovery after bark‐beetle outbreaks.